Exploratory factor analysis for items measuring of the tax auditors’ performance - Ahmad, Mohmad Hazar; Mustapha, Mazlina; Yusri, Yusniyati; Kharuddin, Saira (Penerbit Kolej Universiti Islam Antarabangsa Selangor, 2024)
Tax auditors play an essential role in tax audits to ensure governments can overcome non-tax compliance issues and protect tax revenues for the nation. Tax auditors are expected to perform their tasks efficiently and effectively in examining the taxpayer’s declaration. The tax auditors' performance determines the success of tax audit implementation. Several factors can influence the tax auditors’ performance, including auditors’ effort, professional skepticism and task complexity. Therefore, this study aims to develop a valid and reliable research instrument to measure tax auditors’ performance using the Exploratory Factor Analysis and internal reliability test (Cronbach’s Alpha). A total of 100 tax auditors from the Inland Revenue Board of Malaysia and the Royal Malaysian Customs Department were selected as respondents to participate in this study. The data was collected using the online Google Forms with 5 Likert scales and was analyzed using IBM-SPSS Version 27. The results show that out of 34 developed items, only 30 remained as constructed items. The remaining items were deleted due to the low loading factor of less than 0.40. Thus, this study validated the research instrument to proceed with the Confirmatory Factor Analysis (CFA) in the following step using the validated research instrument